Honouring the life stage of the Crone: self-revelatory performance as rite of passage - De Beer, Welma (My University, 2016)
This study gave expression to my initiatory journey into the last life-cycle of my life, as archetypally represented by the Crone (Prétat, 1994:7–11). It is a personal journey that engages with a specific research question: In what ways can Drama Therapy facilitate the contemplation and initiation of the “Crone” as life stage through self-revelatory performance? Two essential questions frame this study: How can Drama Therapy help us to create a process that contains the inherent destruction that forms part of transformation? If so, what would be the elements and methods that can help facilitate such a process? These questions will be investigated through a creative project, using the method of Performance as Research and the form of self-revelatory performance. The self-revelatory performance engaged with autobiographical moments from my own life and focussed on the theme of transformation. This research report seeks to extrapolate and evaluate the process for the purposes of defining the role and function of drama therapy as self-revelatory performance. The work of Rene Emunah (2009) on the self-revelatory play as a tool for Drama Therapy serves as foundation for this research. Other writings which influenced the study were the work of Victor Turner (Schechner,1993) on liminality, Richard Schechner (1976) on ritual and performance, anthropology of performance and environmental space, Kabi Thulo (2009) on shamanism, Willmar Sauter (2000) on the Theatrical Event and Jacob Moreno’s idea of the Encounter (Kristofferson, 2014). Key concepts that will be investigated are: Jung’s concept of transformation and how it expresses itself through rites of passage, initiation and ritual, myth and storytelling, the crone archetype and self-revelatory theatre. The study’s research findings were derived from the processes of devising, performance and post-performance “insights” which form a part of this creative project. Essentially, this study suggests possible processes that can be used effectively in drama therapy to create a “rite of passage”, “honouring” a new life stage that can “reprogram” or transform us. The study posits that transformation is contained and facilitated when we are able to self-reflect on our history, thoughts, beliefs and cultural coding. Self-revelatory playmaking can be a valuable tool in drama therapy which holds the potential to assist cathartic self-reflection in a safe space (Emunah, 1994:225). This study provides a qualitative description of the phenomena of self-revelatory v playmaking and performance and grapples with how it creates a “rite of passage” to facilitate the transitioning into the last phase of life.
A research report submitted Welma de Beer, student number 1296294, to Drama for Life, Wits School of Arts in partial fulfilment of the requirement of a Master of Arts in drama therapy degree by course work and research report.
Keywords: Drama--Therapeutic use; Narrative therapy; Psychotherapy; Archetype (Psychology); Self